2017
DOI: 10.1177/1750481317691858
|View full text |Cite
|
Sign up to set email alerts
|

Resolving a gender and language problem in women’s leadership: Consultancy research in workplace discourse

Abstract: This paper considers the contribution that consultancy research might make to resolving communication problems that women have identified in their leadership practices. Within the intersecting fields of gender and language and workplace discourse, consultancy researchthat is, practitioner-commissioned research to resolve work-related, communication problemsis still uncommon. This paper presents a study of Monika, a senior leader in an engineering company, who commissioned me to find out why she was experiencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Second, discourse analytical knowledge can make visible, and thus actionable, issues in management that are complex and hard to account for, such as problems related to the multicultural workplace (Angouri, 2018) or female leadership (Baxter, 2017). To achieve this, I again call for increased interdisciplinary efforts between business and management educators and those who have made language and discourse their profession and object of research.…”
Section: Language and Discourse Awareness In Management Education 20mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, discourse analytical knowledge can make visible, and thus actionable, issues in management that are complex and hard to account for, such as problems related to the multicultural workplace (Angouri, 2018) or female leadership (Baxter, 2017). To achieve this, I again call for increased interdisciplinary efforts between business and management educators and those who have made language and discourse their profession and object of research.…”
Section: Language and Discourse Awareness In Management Education 20mentioning
confidence: 99%
“…First, discourse analytical knowledge empowers people to notice and make explicit previously unnoticed phenomena: Llewellyn and Harrison (2006), for example, surveyed employees about their impressions of public relations and corporate documents and found that their interviewees spoke “more explicitly and confidently about aspects of language where they had a grasp of relevant terminology” (p. 580). Second, discourse analytical knowledge can make visible, and thus actionable, issues in management that are complex and hard to account for, such as problems related to the multicultural workplace (Angouri, 2018) or female leadership (Baxter, 2017). To achieve this, I again call for increased interdisciplinary efforts between business and management educators and those who have made language and discourse their profession and object of research.…”
Section: Language Awareness Discourse Awareness and Beyondmentioning
confidence: 99%
“…Women are also subdued in a social position, positioned to be inferior to men (Wardaugh & Fuller, 2015). Meanwhile, in terms of leadership, a woman leader is considered less competent than a male leader and is labeled as "the other" (Baxter, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The results show that there are differences between men and women in terms of language use and the way media shape perception of society toward female politicians. Baxter (2010) and Baxter (2017) also did research about female leadership language. The first research found out that apologetic language pattern styles is often used by women leaders in corporation.…”
Section: Introductionmentioning
confidence: 99%